The influence of the EU on the evolution of national employment models - Rubery, Jill; Bosch, Gerhard; Lehndorff, Steffen (Geneva, 2008)
"This paper focuses on the role of the European Union in promoting and shaping the direction of change and reform of European employment models. The EU has taken on and developed a reform agenda for European employment models, with the vision for their future encapsulated within the guidelines and rhetoric associated with the Lisbon agenda and in particular the European Employment Strategy (EES)."